Compreensão leitora em concurso público - Barbosa, Fábio Gomes (2008)
The dissertation herein inserts in the research line of Portuguese Language Reading, Writing and Teaching and is aimed to analyze the strategies required to applicants in public auctions, for issues related to comprehension in Portuguese reading tests. In order to accomplish our study, we based on Textual Linguistic. To be the corpus of the research we have selected questions of textual comprehension from tests of three public auctions: Banco do Brasil, Caixa Econômica Federal and Tribunal Regional Eleitoral. Results indicate that the applicants are requested to apply several strategies, among which one can highlight: definition of the reading purposes, determination of the main idea, activation of former acquirements, prevision fulfillments about the text, summary generation, question formulation, inference generation, local coherence construction and over-structure activation. Generally speaking, the dissertation highlights the importance of teaching reading strategies so to form active and proficient readers. The comprehension of different texts under different situations requires the knowledge of reading strategies, as it specifically occurs in public auctions